The Problem of Understanding: F. Schleiermacher and the Development Hermeneutics - Šaulauskas, Marius Povilas (Problemos, 1988)
The way in which the problem of hermeneutics is dealt with in F. Schleiermacher’s philosophy is being analysed in the article. The origins of F. Schleiermacher’s conception of understanding as well as its influence on later studies of hermeneutics are considered. The solution of the problem is viewed in the revelation of the essential structures of philosophical discourse.